2021
DOI: 10.3390/plants10020368
|View full text |Cite
|
Sign up to set email alerts
|

Underutilized Mexican Plants: Screening of Antioxidant and Antiproliferative Properties of Mexican Cactus Fruit Juices

Abstract: Cacti fruits are known to possess antioxidant and antiproliferative activities among other health benefits. The following paper evaluated the antioxidant capacity and bioactivity of five clarified juices from different cacti fruits (Stenocereus spp., Opuntia spp. and M. geomettizans) on four cancer cell lines as well as one normal cell line. Their antioxidant compositions were measured by three different protocols. Their phenolic compositions were quantified through high performance liquid chromatography and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The fruits of E. chiotilla are important edible resources with anticancer properties (Sandate-Flores et al, 2020). Furthermore, pitaya has also drawn attention for its potential nutraceutical properties since it has natural pigments (betalains), vitamin C, high contents of iron and phenolic compounds, and antiproliferative activity on human cancer cell lines (García-Cruz et al, 2013Martínez et al, 2021). The pitaya and jiotilla are highly valued in the region because the fruits are an important source of income for communities (Chuck-Hernández et al, 2016;García-Suárez et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The fruits of E. chiotilla are important edible resources with anticancer properties (Sandate-Flores et al, 2020). Furthermore, pitaya has also drawn attention for its potential nutraceutical properties since it has natural pigments (betalains), vitamin C, high contents of iron and phenolic compounds, and antiproliferative activity on human cancer cell lines (García-Cruz et al, 2013Martínez et al, 2021). The pitaya and jiotilla are highly valued in the region because the fruits are an important source of income for communities (Chuck-Hernández et al, 2016;García-Suárez et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…From hand‐peeled O. ficus‐indica fruit, Moßhammer, Stintzing, and Carle (2006) developed a canned product. Martínez et al (2021) made clarified juices from different cactus species. Cactus fruits can also be used to produce cakes, bread, jams, sweets, yogurt, ice cream, alcoholic beverages, nectars, and sweeteners, as presented by de Araújo, de Paulo Farias, Neri‐Numa, and Pastore (2021), Amaya‐Cruz et al (2019), and Andreu, Nuncio‐Jáuregui, Carbonell‐Barrachina, Legua, and Hernández (2018).…”
Section: Resultsmentioning
confidence: 99%
“…juice displayed cytotoxic effect on a liver cancer cell line no toxic effect on fibroblasts (Martínez et al, 2021). Cladodes ethanolic extract improved methotrexate (MTX) induced testicular injury in rats through its protective actions on rat's testis histology, oxidative stress and improvement of both sperms motility and count and serum testosterone levels (Akacha et al, 2020).…”
Section: Ta B L E 6 (Continued)mentioning
confidence: 99%
“…El‐Beltagi et al (2019) reported that the percentage of viability of different cancer cell lines including colorectal adenocarcinoma (Caco‐2), liver cell line (HepG2) and breast cell line (MCF‐7) was decreased with increasing pulp and peel ethanolic extracts concentrations (500, 1,000, 1,500, 2,000, 3,000 μg/ml) with the higher activity of pulp relative to peel. OFI yellow clarified fruit juice displayed selective cytotoxic effect on a liver cancer cell line with no toxic effect on fibroblasts (Martínez et al, 2021). Cladodes ethanolic extract improved methotrexate (MTX) induced testicular injury in rats through its protective actions on rat's testis histology, oxidative stress and improvement of both sperms motility and count and serum testosterone levels (Akacha et al, 2020).…”
Section: Biological Activitiesmentioning
confidence: 99%